J.F Ade Ajavi and the UNESCO general history of Africa: some personal reflections - Ahmed Ibrahim, Hassan (Bookcraft, 2014)
This is a book on the life and career of Professor J. F. Ade Ajayi, a distinguished historian, administrator, intellectual and builder of institutions; a renaissance man and a gentleman. Written by a collection of Professor Ajayi's former students, academic colleagues, members of his family, his associates and friends, contributors approach the subject from different perspectives and angles, without sacrificing the focus on the man and his career.